Risk Factors Causing Unintentional Home Injuries in Children Under 5 Years of Age Presenting to Emergency Department of Ziauddin University Hospital - Hira Khan, Hifza Aiman, Shaista Ehsan, Afreena Qureshi, Syed Ibrahim Bukhari, Sana Faheem (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the predisposing factors contributing to unintentional home injuries in children under 5 years of age presenting to Emergency department of Ziauddin medical university and hospital, Karachi Place and duration of study: The study is conducted at Department of Emergency, Ziauddin Medical University and Hospital, Karachi And the duration of study is 13th October 2019 To 12th April 2020. It is a cross-sectional study design having having 200 patients, in which non-probability consecutive sampling technique is used. Material and Method: There were 200 patients in total with Injuries that happened at home environment. Mothers participated in an interview. After each child received the recommended care, data were gathered.Calculated descriptive statistics were used. Stratification was used to manage effect modifiers. The chi-square test was used after stratification. P-values lower than 0.05 were regarded as significant. Results: There were 46% male and 54% female patients. Mean age was 35.02±13.79 months. Most of the children were injured >3 times in last one month. 57% patients were found with injury due to falling down while most of the injuries (32.5%) were occurred at stairs. In our study, 39% of children caused injury due to lack of care, 11.5% due to availability of hazardous material and 49.5% due to unsafe home environment. Practical implications: From the standpoint of injury prevention, this study suggests that the risk of non-fatal injury in children under the age of five is complicated and multidimensional, and that effective prevention measures must target numerous components. To effectively increase children’s comprehension of the safety issue and lower their risk of hazard, health care providers, parents, or both should design alternative strategic teaching methods. Conclusion: Most prevalent cause of injury was falling down. 39% children injured due to lack of care, 11.5% due to availability of hazardous material and 49.5% due to unsafe home environment. Keywords: Unintentional Home injuries, Children, predisposing factors, falling down, Injuries